APLICATION OF BREAK EVENT POINT METHOD TO ANALYZE THE FEASIBILITY OF ESTABLISHING A BUSINESS PRODUCING BIO CHARCOAL COCONUT SHELL BRIQUETTE CONTINUOUS SYSTEM USING AN EXTRUDER MACHINE - MADE, WIJANA; Syahrul,; Sinarep,; I.W, Joniarta; I.P.B, Pramartha (Journal of Industrial Engineering and Innovation, 2025)
In general, biocharcoal briquettes are made from various industrial wastes and are made on a small scale, traditionally and never made on an industrial scale using Business Feasibility Analysis. While some wastes that have the potential to become alternative energy, are abundant, and have high energy value tend not to be utilized, among these wastes is cow dung. For this reason, a study was conducted on making briquettes from cow dung (KS) and coconut shells (TK). The two raw materials, after being charcoaled, were then crushed and filtered with a sieve to obtain a charcoal grain size of 20 mesh according to the best size from previous research, and mixed with variations in the % weight composition of KS: TK, namely 25:75, 50:50 and 75:25. and then tested for calorific value in the laboratory. The best briquettes will be produced on an industrial scale using an extruder printing machine, so that a continuous printing process is obtained. Furthermore, a BEP analysis will be carried out to determine the feasibility of establishing a briquette production business. The results of this study obtained that the most recommended biochar briquettes to be produced are briquettes with a variation of sago adhesive mixture with a percentage of 25% KS: 75% TK with a calorific value of 5,574 cal/g, and the results of the BEP analysis obtained the total production units that must be made so that the biochar briquette making business using an extruder machine is at the break-even point is 8,517 kg of biochar briquettes. and with a production of 1320 kg/month, the time to reach BEP is in the 6.45th month, this shows that establishing a biocharcoal briquette manufacturing business using an extruder machine is feasible.